Lessons Learned From Dear Pandemic, a Social Media–Based Science Communication Project Targeting the COVID-19 Infodemic. (May 2022) - Albrecht, Sandra S.; Aronowitz, Shoshana V.; Buttenheim, Alison M.; Coles, Sarah; Dowd, Jennifer Beam; Hale, Lauren; Kumar, Aparna; Leininger, Lindsey; Ritter, Ashley Z.; Simanek, Amanda M.; Whelan, Christine B.; Jones, Malia
The World Health Organization has identified excessive COVID-19 pandemic–related information as a public health crisis, calling it an "infodemic." Social media allows misinformation to spread quickly and outcompete scientifically grounded information delivered via other methods. Dear Pandemic is an innovative, multidisciplinary, social media–based science communication project whose mission is to educate and empower individuals to successfully navigate the overwhelming amount of information circulating during the pandemic. This mission has 2 primary objectives: (1) to disseminate trustworthy, comprehensive, and timely scientific content about the pandemic to lay audiences via social media and (2) to promote media literacy and information-hygiene practices, equipping readers to better manage the COVID-19 infodemic within their own networks. The volunteer team of scientists publishes 8-16 posts per week on pandemic-relevant topics. Nearly 2 years after it launched in March 2020, the project has a combined monthly reach of more than 4 million unique views across 4 social media channels, an email newsletter, and a website. We describe the project's guiding principles, lessons learned, challenges, and opportunities. Dear Pandemic has emerged as an example of a promising new paradigm for public health communication and intervention. The contributors deliver content in ways that are personal, practical, actionable, responsive, and native to social media platforms. The project's guiding principles are a model for public health communication targeting future infodemics and can bridge the chasm between the scientific community and the practical daily decision-making needs of the general public.